Effect of information about sexual assault presentation specificities on female students’ attitude towards sexual assault - Mitaitė, A.; Žardeckaitė-Matulaitienė, K. (Psichologija, 2013)
The aim of the study was to determine the effect of the characteristics of a rapist and a victim on the sexual assault assessment of female students. 200 respondents participated in the research. 43.5% of them were 1st year, 52.0% – 2nd year, 3.5% – 3rd year, and 1st–4th year female students of the Vytautas Magnus University. Their average age was 19.89 years (SD 1.009). The respondents have been presented with a research instrument composed of demographic questions, sexual assault scenarios of A. Wilkinson (8 versions), and questions related to the sexual assault scenarios. Each scenario was followed by five scales: Behavioral Blame (BB), Character Blame (CB), Punishment (P), Victim Reporting (VR), and Reporting (R). Each scale consisted of three questions, and responses were obtained on a 7-point Likert scale. All scenarios contain an identical sexual assault situation. However, three characteristics are manipulated with: 1) the victim is acquainted/unacquainted with the rapist, 2) the victim is sober / under the influence, 3) the sexual assault is defined by the term of rape / unwanted sex. The results of the research show that victims of sexual assault are assessed unequally. It has been found that sexual assault victims are blamed for their behavior as being more provocative for the sexual assault when they know the rapist (β = –0.412; p = 0.0001) and the term “unwanted sex” is used (β = 0.173; p < 0.009) in comparison with the situation when the rapist is a stranger and the assault is defined as “a rape”. Similarly, sexual assault victims are blamed for their character as being more responsible for the sexual assault when they know the rapist (β = -0.156; p = 0.024), and the term “unwanted sex” is used (β = 0.246; p = 0.001) in comparison with the situation when the rapist is a stranger and the assault is defined as “a rape”. However, the fact that the victim has consumed / not consumed alcohol does not have a significant effect on her blame (p > 0.05). Also, it has been found that the rapist is more responsible and deserving a stricter punishment, when the term “rape” is used, in comparison with the term “unwanted sex” (β = –0.363; p < 0.0001), and this issue has a more significant effect than the victim’s relation with the rapist (β = 0.285; p < 0.0001) or the victim’s condition (consumed / not consumed alcohol) (p < 0.05). Lastly, respondents think that the victim tends to report sexual assault more often when the term “rape” is used (β = –0.330; p < 0.0001) and the rapist is unacquainted with the victim (β = 0.203; p = 0.002). Also, respondents hypothetically think that they personally would report about a sexual assault more often when they would be sober (β = 0.150; p = 0.033), they would not know the rapist (β = 0.157; p = 0.023), and the term “rape” would use (β = –0.232; p = 0.001). Additionally, respondents’ demographic characteristics (the year of study and the study field) were not significant predictors of their attitudes towards sexual assault (p < 0.05).